Dinamika Konflik Kerja dalam Usaha Mikro: Studi Kasus pada Toko Daging Kuniku Meat di Semarang - Dimaciela Vistanada Sekarlangit; Andriyani Andriyani (Diponegoro Journal of Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) serve as the backbone of Indonesia’s economy, contributing significantly to the national Gross Domestic Product (GDP) and employment. MSMEs in Indonesia have demonstrated remarkable adaptability during times of crisis, playing a crucial role in economic recovery. This study aims to examine the dynamics of workplace conflict at Kuniku Meat Butcher Shop in Semarang. This research adopts a qualitative approach using a case study method. The subjects were selected through purposive sampling, specifically targeting the owner and employees of Kuniku Meat. Data were gathered through three main techniques: in-depth interviews, direct observation, and document analysis. The data were then analyzed using thematic analysis—a method for identifying, categorizing, and interpreting key themes within qualitative data. The findings indicate that workplace conflict at Kuniku Meat reflects the typical dynamics of micro-enterprises with informal organizational structures. The conflicts identified include interpersonal, structural, and emotional aspects. Work relationships based on familial ties and the absence of formal systems have led to unclear roles, mutual blame, and emotional tensions between the owner and the employees.